Clinical implications of near-infrared fluorescence imaging in cancer - Kosaka, Nobuyuki (2009)
Near-infrared (NIR) fluorescence cancer imaging is a growing field for both preclinical and clinical application to the clinical management for cancer patients due to its advantageous features, including a high spatial resolution, portability, real-time display and detailed molecular profiling with the multiplexed use of fluorescent probes. In this review, we present a basic concept of NIR fluorescence imaging and overview its potential clinical applications for in vivo cancer imaging, including cancer detection/characterization, lymphatic imaging (sentinel lymph node detection) and surgical/endoscopic guidance. NIR fluorescence imaging can compensate some limitations of conventional imaging modalities, and thus it could play an important role for cancer imaging combined with other modalities in clinical practice.